2021
DOI: 10.3390/diagnostics11122346
|View full text |Cite
|
Sign up to set email alerts
|

In-House Immunofluorescence Assay for Detection of SARS-CoV-2 Antigens in Cells from Nasopharyngeal Swabs as a Diagnostic Method for COVID-19

Abstract: Immunofluorescence is a traditional diagnostic method for respiratory viruses, allowing rapid, simple and accurate diagnosis, with specific benefits of direct visualization of antigens-of-interest and quality assessment. This study aims to evaluate the potential of indirect immunofluorescence as an in-house diagnostic method for SARS-CoV-2 antigens from nasopharyngeal swabs (NPS). Three primary antibodies raised from mice were used for immunofluorescence staining, including monoclonal antibody against SARS-CoV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The presence of the nucleocapsid (indirect immunofluorescence positivity) (but not RBD) correlates with the viral load (RT-PCR). On the other hand, no trend was seen for some samples, probably due to the quality of these samples (Lam et al, 2021).…”
Section: Discussion Of the Microscopy Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…The presence of the nucleocapsid (indirect immunofluorescence positivity) (but not RBD) correlates with the viral load (RT-PCR). On the other hand, no trend was seen for some samples, probably due to the quality of these samples (Lam et al, 2021).…”
Section: Discussion Of the Microscopy Resultsmentioning
confidence: 88%
“…Microscopy can be used as a tool for the development of rapid detection assays as numerous techniques are available in this field. Lam et al, 2021 demonstrated the potential of immunofluorescence as a simple diagnostic tool; however, due to sensitivity problems, other detection methods have to be developed (Arevalo- Rodriguez et al, 2020).…”
Section: The Need Of Developing Rapid Sars-cov-2 Screening Methods Us...mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a sensitive detection of these biomarkers can greatly improve the disease diagnosis and provide a more objective and quantifiable basis for clinical decision-making. However, most of the current detection methods, such as the enzyme-linked immunosorbent assay (ELISA) [ 4 ], the high-performance liquid chromatography (HPLC) [ 5 ] and the immunofluorescence assay (IFA) [ 6 ], have problems involving a lengthy consumption, complex steps, a low sensitivity, and radioactive pollution, which cannot be used to detect these trace substances. Moreover, some detection processes need secondary labeling, which has potential radiation hazards.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of biochemical sensors provides a feasible solution for the rapid, sensitive and efficient detection and analysis of the disease-related microbiomarkers. Compared with the traditional detection methods, biochemical sensors are more and more widely used to detect various trace substances due to their advantages in offering a fast response, high sensitivity, strong specificity, a label-free detection and less sample demand [ 6 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%